Quantitative and descriptive comparison of four acoustic analysis systems: vowel measurements - Burris, Carlyn (2014)
PURPOSE: This study examines accuracy and comparability of four trademarked acoustic analysis software packages (AASP): Praat, Wavesurfer, TF32 and CSL using synthesized and natural vowels. Features of AASP are also described. METHODS: Synthesized and natural vowels were analyzed using each of AASP’s default settings to secure nine acoustic measures: fundamental frequency (F0), formant frequencies (F1-F4), and formant bandwidths (B1-B4). The discrepancy between the software measured values and the input values (synthesized, previously reported, and manual measurements) was used to assess comparability and accuracy. Basic AASP features are described. RESULTS: Results indicate that Praat, Wavesurfer, and TF32 generate accurate and comparable F0 and F1-F4 data for synthesized vowels and adult male natural vowels. Results varied by vowel for adult females and children, with some serious errors. Bandwidth measurements by AASPs were highly inaccurate as compared to manual measurements and published data on formant bandwidths. CONCLUSIONS: Values of F0 and F1-F4 are generally consistent and fairly accurate for adult vowels and for some child vowels using the default settings in Praat, Wavesurfer, and TF32. Manipulation of default settings yields improved output values in TF32 and CSL. Caution is recommended especially before accepting F1-F4 results for children and B1-B4 results for all speakers.